Pengaruh Penjualan Kredit dan Perputaran Piutang terhadap Profitabilitas Periode Sebelum dan Saat Covid-19: (Studi pada Perusahaan Sub Sektor Kosmetik dan Keperluan Rumah Tangga yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2021) - R. Enough Bhaktiar; Nia Kusniati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The research was conducted on companies in the cosmetics and household needs subsector listed on the Indonesia Stock Exchange in 2015-2021. This type of research uses quantitative methods samples selected using purposive techniques. Data analysis is done using panel data regression with the help of the Eviews 12 program. The research results indicate that partially, Credit Sales and Accounts Receivable Turnover has no effect on profitability, while simultaneously, Credit Sale and Accounts Receivable Turnover show a positive and significant effect on profitability (return on asset) with a determination coefficient of 0,631977 or 63,1977% then the remaining 0,368023 or 36,8023% is influenced by other variables that are outside this study.